Emotional Intelligence, Familial Background and job performance - Evidence from Professional Managers in China - Ma, S.; Trigo, V.; Silva, M. Gabriela (GEMRev Brown-bag Seminar, 2014)
This GEMRev Brown bag seminar presents preliminary results of an ongoing study that uses the same sample – 243 professional managers in mainland China – to explore two different lines of research related to the issue of emotional intelligence (EI). The first line of research stems from the idea that familial environment deeply affects a child’s cognitive development and the second line of research relates emotional intelligence to job performance. Respondents provided information on their EI score by using the WEIS, an EI scale developed for Chinese respondents. The EI scores were compared to demographic characteristics of the individuals (age, sex, marital status, only-child, employers’ ownership, position, parents’ level of education, and parents’ occupation).